PERLINDUNGAN HUKUM MEREK PRODUK TENUN IKAT MEDALI MAS PADA UD. MEDALI MAS KOTA KEDIRI - Salsabila Cahyawati Nur Hanifah; Hernawan Hadi (Jurnal Privat Law, 2026)
This articles aims to determine the legal protection of the Medali Mas brand of ikat products produced by the UD. Medali Mas according to the legal provisions in force in Indonesia based on Undang-Undang Nomor 20 Tahun 2016 Tentang Merek dan Indikasi Geografis as well as regarding the obstacles in the implementation of protection. trademark law. This research is a prescriptive normative legal research. The approach used is a statutory approach. The sources of legal materials used are primary legal materials and secondary legal materials. The analysis of legal materials used is a data analysis technique with deductive logic. The rise of plagiarism of trademarks with each other has made the protection of the products weaving mark produced by UD. Medali Mas must be carried out immediately so that legal protection is created in accordance with Law Number 20 of 2016 concerning Marks and Geographical Indications. The results showed that the Medali Mas trademark did not receive legal protection in the Act due to not being legally registered with the Directorate General of Intellectual Property, this was due to various obstacles that occurred so that the process of implementing brand protection was hampered.